Indians in the Fur Trade: Their Role as Trappers, Hunters, and Middlemen in the Lands Southwest of Hudson Bay, 1660-1870: with a new introduction - Ray, Arthur J. (Canada 150 Collection, 2017)
First published in 1974, this best-selling book was lauded by Choice as 'an important, ground-breaking study of the Assiniboine and western Cree Indians who inhabited southern Manitoba and Saskatchewan' and 'essential reading for anyone interested in the history of the Canadian west before 1870.' Indians in the Fur Trade makes extensive use of previously unpublished Hudson's Bay Company archival materials and other available data to reconstruct the cultural geography of the West at the time of early contact, illustrating many of the rapid cultural transformations with maps and diagrams. Now with a new introduction and an update on sources, it will continue to be of great use to students and scholars of Native and Canadian history. --Publisher's description

The Fur Trade in Canada: An Introduction to Canadian Economic History - Innis, Harold Adams; Ray, Arthur J. (University of Toronto Press, 1999)
At the time of its publication in 1930, The Fur Trade in Canada challenged and inspired scholars, historians, and economists. Now, almost seventy years later, Harold Innis's fundamental reinterpretation of Canadian history continues to exert a magnetic influence. Innis has long been regarded as one of Canada's foremost historians, and in The Fur Trade in Canada he presents several histories in one: social history through the clash between colonial and aboriginal cultures; economic history in the development of the West as a result of Eastern colonial and European needs; and transportation history in the case of the displacement of the canoe by the York boat. Political history appears in Innis's examination of the nature of French-British rivalry and the American Revolution; and business history is represented in his detailed account of the Hudson's Bay and Northwest Companies and the industry that played so vital a role in the expansion of Canada. In his introduction to this new edition, Arthur J. Ray argues that The Fur Trade in Canada is the most definitive economic history and geography of the country ever produced. Innis's revolutionary conclusion - that Canada was created because of its geography, not in spite of it - is a captivating idea but also an enigmatic proposition in light of the powerful decentralizing forces that threaten the nation today. Ray presents the history of the book and concludes that "Innis's great book remains essential reading for the study of Canada. --Publisher's description. Includes bibliographical references (p. [421]-441) and index.
Keywords: Fur trade -- Canada -- History